RESEARCH AND DESIGN OF AN EFFICIENT ADAPTIVE DRIVE WITH BALANCING FRICTION COUPLING - Alipbayev, Kuanysh; Ivanov, Konstantin; Sultan , Aidos; Komekbayev , Arman (Journal of Applied Engineering Science, 2024)
Currently, research related to the automation of processes, systems and devices are of high relevance in the scientific and technical field: in the aerospace industry, robotics and electric transport technology. Successful automation of facilities and processes requires simplified control systems, and an adaptive mechanical system operates without a control system, which increases its reliability and efficiency. In particular, the creation of an efficient and reliable transmission of electric autonomous and mobile vehicles can be achieved by an adaptive mechanical drive with two degrees of freedom. Adaptation of the two-mobile system (2-DoF) is achieved by the proposed completely new type of transmission, namely the design of a stepless multi-speed drive with an additional friction coupling. The property of reliable adaptation of a two-mobile self-adjusting mechanical drive is independent adaptability to an external load with the help of a balancing friction coupling that provides a connection between the frictional moment and the relative angular velocity. The article presents a study of the interaction of the parameters of a two- mobile system in order to improve the efficiency of a self-adjusting adaptive drive with a given wide range of regulation based on the use of a friction coupling.